Evaluation of Plio-Quaternary uplift of the South-Eastern Caucasus based on the study of the Akchagylian marine deposits and continental molasses. (20th December 2021) - Trikhunkov, Ya.I.; Kangarli, T.N.; Bachmanov, D.M.; Frolov, P.D.; Shalaeva, E.A.; Latyshev, A.V.; Simakova, A.N.; Popov, S.V.; Bylinskaya, M.E.; Aliyev, F.A.
Abstract: The highest Shahdag-Qusar segment of the South-Eastern Caucasus, located on the border of Azerbaijan and Russia, is considered. Ridges of Greater Caucasus axial zone are the closest to the Caspian Sea coast here, and the latest marine deposits cover the high-mountainous watershed surfaces. Research results of the Plio-Quaternary tectonic movements and stratigraphy are presented. Morphostructural and facies analysis of the northern macro-slope of the mountain system was performed to reconstruct the history of Plio-Quaternary orogenesis of this territory. Findings of shells of molluscs, an indicator of the Akchagylian basin, in the sediments of the homoclinal Qusar plateau at altitudes up to 2020 m asl made it possible to estimate the rate of the Quaternary uplift in the South-Eastern Caucasus and compare these data with the results of previous studies in Transcaucasia. The reconstruction of the mountain system development in the Pliocene with acceleration of the average Pliocene uplift is presented, and the probable reasons for this acceleration are discussed.